Deviations from uncovered interest parity: A Kalman filter approach to the Mark/Dollar rate and the Swiss Franc/Dollar rate - Peter König; Joachim Möller (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1988)
The present paper analyzes deviations from Uncovered Interest Parity by applying a Kalman filter procedure based on optimal initial information to the estimation of this arbitrage equilibrium for the Mark/Dollar rate and the Swiss Franc/Dollar rate. The results demonstrate that the hypothesis of a time-varying deviation from Uncovered Interest Parity in these equations cannot be rejected. Furthermore, these models are shown to out-perform the random walk in forecasting. An examination of the stochastic disturbances indicates that the shocks responsible for the deviations cover a wide range of economic and political issues.
Keywords: 330